PENGARUH AVERAGE COLLECTION PERIOD, AVERAGE PAYMENT PERIOD, TURNOVER IN DAYS, SALES GROWTH DAN DEBT RATIO TERHADAP PROFITABILITAS PERUSAHAAN - Harapan, Anthonius; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
This purpose of this research is to analyze the influence of average collection period, average payment period, average inventory turnover in days, sales growth and the debt ratio on profitability in companies listed on the Indonesian Stock Exchange. The population in this research are all manufacturing companies listed in Indonesia Stock Exchange period 2010-2014. The research sample consisted of 116 companies per year listed in the Indonesia Stock Exchange so that the total observation data for 5 years are 580 data. The data used in this research is secondary data and sample selection using purposive sampling method. The analysis model used is multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and profitability. Using t-test to examine the partial correlation of each independent variable on profitability. Based on the results of the analysis showed that the variables average collection period, average paymen period, average inventory turnover in days and the debt ratio has a significant effect on profitability, while sales growth has no significant effect on profitability.